Knowledge management and pedagogical innovativeness of vocational educators, the mediating role of transformational leadership style - Helen Edowaye Chukwuemeke; Navid Nwanna Dumbiri (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The study investigated the relationships on three dimensions of knowledge management (KM), pedagogical innovativeness (PI) and transformational leadership style (TLS) Design used for the study was correlational and data were collected from 137 vocational educators/lecturers in public universities in Nigeria, this forms the sample of study. Structured questionnaire was instrument used, covering the demographic variables of the respondents and measured the relevant dimensions of knowledge management, pedagogical innovativeness and transformational leadership style. Three experts face validated instrument for study. The reliability was measured using Cronbach alpha method and an overall alpha value of 0.89 was obtained. The data was collected by the authors and analysed. Bivariate correlation linear regression and path analysis via 5000 re-samples bootstrap method was used for analysis. The results showed that knowledge management dimensions i.e. knowledge dissemination, responsiveness to knowledge predict significantly pedagogical innovativeness while knowledge acquisition did not significantly predict pedagogical innovativeness. It also showed that transformational leadership style does mediate relationship between knowledge management and pedagogical innovativeness. The results suggest that knowledge acquisition (KA), knowledge dissemination (KD) responsiveness to knowledge (RK) are among the key indicators of pedagogical innovativeness. The result also suggest that low transformational leadership style will not bring about the relationship between knowledge management and pedagogical innovativeness. Based on findings it was recommended that knowledge management should be encourage in tertiary institutions as this will enhanced pedagogical innovativeness of vocational educators. Also, management of tertiary institution should employ transformational leadership style for ultima productivity of their employees.